2018
DOI: 10.1177/2158244018778110
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Contracts of Multiple Jobholders: A Multilevel Analysis

Abstract: Organizational research has paid little attention to multiple jobholders. This study investigated the psychological contracts of multiple jobholders in relation to each employment contract and the nonstandard work arrangement of multiple jobholding. The sample consisted of 141 multiple jobholders with two or more jobs and either employed or self-employed status. The results of the multilevel analyses indicated that, with one exception, psychological contract obligations vary more between employment relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 50 publications
0
13
0
2
Order By: Relevance
“…The case study increased knowledge of the under-researched themes of workplace learning and career development among multiple jobholders. The research literature on MJH has been mainly economic and quantitative and concentrated on the labour market and individual perspectives, whereas organization and learning studies have paid little attention to that group (Bamberry and Campbell, 2012; Panos et al , 2014; Raeder, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The case study increased knowledge of the under-researched themes of workplace learning and career development among multiple jobholders. The research literature on MJH has been mainly economic and quantitative and concentrated on the labour market and individual perspectives, whereas organization and learning studies have paid little attention to that group (Bamberry and Campbell, 2012; Panos et al , 2014; Raeder, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although MJH may forecast career transitions (Panos et al , 2014), the experiences of psychological contract obligations have been observed to vary more between employment relationships than between individuals (Raeder, 2018). Therefore, MJH does not necessarily mean commitment risks for employers.…”
Section: Multiple Jobholdingmentioning
confidence: 99%
See 3 more Smart Citations